Evaluating the accuracy and precision of sonographic fetal weight estimation models in extremely early‐onset fetal growth restriction. (20th November 2019) - Warrander, Lynne K.; Ingram, Emma; Heazell, Alexander E. P.; Johnstone, Edward D.
Abstract: Introduction: Birthweight is a critical predictor of survival in extremely early‐onset fetal growth restriction (diagnosed pre‐28 weeks' gestation, with abnormal umbilical/uterine artery Doppler waveforms), therefore accurate fetal weight estimation is a crucial component of antenatal management. Currently available sonographic fetal weight estimation models were predominantly developed in populations of mixed gestational age and varying fetal weights, but not specifically tested within the context of extremely early‐onset fetal growth restriction. This study aimed to determine the accuracy and precision of fetal weight estimation in this population and investigate whether model performance is affected by other factors. Material and methods: Cases where a growth scan was performed within 48 hours of delivery (n = 65) were identified from a cohort of extremely early‐onset fetal growth‐restricted pregnancies at a single tertiary maternity center (n = 159). Fetal biometry measurements were used to calculate estimated fetal weight using 21 previously published models. Systematic and random errors were calculated for each model and used to identify the best performing model, which in turn was used to explore the relationship between error and gestation, estimated fetal weight, fetal presentation, fetal asymmetry and amniotic fluid volume. Results: Both systematic (median 8.2%; range −44.1 to 49.5%) and random error (median 11.6%; range 9.7‐23.8%) varied widely across models. The best performing model was Hadlock head circumference‐abdominal circumference‐femur length (HC‐AC‐FL), regardless of gestational age, fetal size, fetal presentation or asymmetry, with an overall systematic error of 1.5% and random error of 9.7%. Despite this, it only calculated the estimated fetal weight within 10% of birthweight in 64.6% of cases. There was a weak negative relation between mean percentage error with Hadlock HC‐AC‐FL and amniotic fluid volume, suggesting fetal weight is overestimated at lower liquor volumes and underestimated at higher liquor volumes ( P = 0.002, adjusted R 2 = 0.08). Conclusions: Hadlock HC‐AC‐FL is the most accurate model currently available to estimate fetal weight in extremely early‐onset fetal growth restriction independent of gestation or fetal size, asymmetry or presentation. However, for 35.4% of cases in this study, estimated fetal weight calculated using this model deviates by more than 10% from birthweight, highlighting a need for an improved model.